Direct effects of glucagon on glucose uptake and lipolysis in human adipocytes - Pereira, Maria J.; Thombare, Ketan; Sarsenbayeva, Assel; Kamble, Prasad G.; Almby, Kristina; Lundqvist, Martin; Eriksson, Jan W. (Molecular and cellular endocrinology, 2020)
We aim to investigate the expression of the glucagon receptor (GCGR) in human adipose tissue, and the impact of glucagon in glucose uptake and lipolysis in human adipocytes. GCGR gene expression in human subcutaneous and visceral adipose tissue was demonstrated, albeit at low levels and with an inter-individual variation. Furthermore, GCGR expression was not significantly different between subjects with T2D and matched controls, and we found no significant association with BMI. Glucagon only at a supra-physiological concentration (10–100 nM) significantly increased basal and insulin-stimulated glucose uptake by up to 1.5-fold. Also, glucagon (0.01 and 1 nM) dose-dependently increased basal and isoproterenol-stimulated lipolysis up to 3.7- and 1.7-fold, respectively, compared to control. In addition, glucagon did not change insulin sensitivity to stimulate glucose uptake or inhibit lipolysis. In conclusion, we show that the GCGR gene is expressed at low levels in human adipose tissue, and glucagon at high concentrations can increase both glucose uptake and lipolysis in human adipocytes. Taken together, our data suggest that glucagon at physiological levels has minor direct effects on the regulation of adipocyte metabolism, but does not antagonize the insulin effect to stimulate glucose uptake and inhibit lipolysis in human adipocytes. •Glucagon receptor is expressed at low levels in human adipose tissue.•Glucagon at high concentrations increases glucose uptake and lipolysis in human adipocytes.•Glucagon stimulating effects on glucose uptake are independent of insulin signalling.